Investigation of the reduction process of dopamine using paired pulse voltammetry - Kim, Do Hyoung (Journal of electroanalytical chemistry (Lausanne, Switzerland), 2014)
The oxidation of dopamine (DA) around +0.6V potential in anodic sweep and its reduction around -0.1V in cathodic sweep at a relatively fast scanning rate (300 V/s or greater) have been used for identification of DA oxidation in fast-scan cyclic voltammetry (FSCV). However, compared to the oxidation peak of DA, the reduction peak has not been fully examined in analytical studies, although it has been used as one of the representative features to identify DA. In this study, the reduction process of DA was investigated using paired pulse voltammetry (PPV), which consists of two identical triangle-shaped waveforms, separated by a short interval at the holding potential. Especially, the discrepancies between the magnitude of the oxidation and reduction peaks of DA were investigated based on three factors: (1) the instant desorption of the DA oxidation product (dopamine-o-quinone: DOQ) after production, (2) the effect of the holding potential on the reduction process, and (3) the rate-limited reduction process of DA. For the first test, the triangle waveform FSCV experiment was performed on DA with various scanrates (from 400 to 1000 V/s) and durations of switching potentials of the triangle waveform (from 0.0 to 6.0 ms) in order to vary the duration between the applied oxidation potential at +0.6V and the reduction potential at -0.2V. As a result, the ratio of reduction over oxidation peak current response decreased as the duration became longer. To evaluate the effect of holding potentials during the reduction process, FSCV experiments were conducted with holding potential from 0.0V to -0.8V. We found that more negative holding potentials lead to larger amount of reduction process. For evaluation of the rate-limited reduction process of DA, PPV with a 1Hz repetition rate and various delays (2, 8, 20, 40 and 80ms) between the paired scans were utilized to determine how much reduction process occurred during the holding potential (-0.4V). These tests showed that relatively large amounts of DOQ are reduced to DA during the holding potential. The rate-limited reduction process was also confirmed with the increase of reduction in a lower pH environment. In addition to the mechanism of the reduction process of DA, we found that the differences between the responses of primary and secondary pulses in PPV were mainly dependent on the rate-limited reduction process during the holding potential. In conclusion, the reduction process may be one of the important factors to be considered in the kinetic analysis of DA and other electroactive species in brain tissue and in the design of new types of waveform in FSCV